A Critical Appraisal of The Role of Retribution in Aníkúlápó: The Movie - Adedokun, Theophilus Adedayo; Olanrewaju, Abolaji Christianah (Indonesian Journal of Social Research (IJSR), 2023)
This study examines Aníkúlápó, a Yoruba historical movie, to elucidate cultural perspectives on retributive justice. The study is grounded in the Yoruba worldview, which frames retribution as essential for restoring cosmic and social equilibrium when moral norms are violated. The data analysis used textual analysis of Aníkúlápó’s narrative depictions of crime and punishment as insights into traditional Yoruba principles of retributive justice. The findings reveal that the movie accurately portrays customary public punishment processes in precolonial Yoruba society aimed at communal justice and harmony. Beliefs in supernatural forces dispensing divine retribution are also authentically represented. While punishments seek to deter crime and rehabilitate offenders, scholarly critiques note occasional unfairness and excess. Overall, the analysis of the movie illuminates the pivotal role of retribution in Yoruba's cultural identity and moral philosophy. The key themes in the study relate to retribution's links to cosmic balance, supernatural dimensions, and functions as deterrence and rehabilitation. By situating the analysis of Aníkúlápó within scholarship on African jurisprudence, the study elucidates Yoruba perspectives on fate, choice, proportionality, and pragmatism when responding to moral complexities and wrongdoing. This study contributes original humanistic insight into indigenous African philosophies of social harmony beyond punitive justice. This study recommends comparing diverse narratives and contemporary attitudes to enrich the understanding retribution's nuanced cultural significance.